Influence of CO2 and nitrogen limitation on the coccolith volume of Emiliania huxleyi (Haptophyta) - Muller, MN; Beaufort, L; Bernard, O; Pedrotti, ML; Talec, A; Sciandra, A (2012)
Coccolithophores, a key phytoplankton group, are one of the most studied organisms regarding their physiological response to ocean acidification/carbonation. The biogenic production of calcareous coccoliths has made coccolithophores a promising group for paleoceanographic research aiming to reconstruct past environmental conditions. Recently, geochemical and morphological analyses of fossil coccoliths have gained increased interest in regard to changes in seawater carbonate chemistry. The cosmopolitan coccolithophore Emiliania huxleyi (Lohm.) Hay and Mohler was cultured over a range of p CO2 levels in controlled laboratory experiments under nutrient replete and nitrogen limited conditions. Measurements of photosynthesis and calcification revealed, as previously published, an increase in particulate organic carbon production and a moderate decrease in calcification from ambient to elevated pCO2. The enhancement in particulate organic carbon production was accompanied by an increase in cell diameter. Changes in coccolith volume were best correlated with the coccosphere/cell diameter and no significant correlation was found between the coccolith volume and the particulate inorganic carbon production. The conducted experiments revealed that the coccolith volume of E. huxleyi is variable with aquatic CO2 concentration but its sensitivity is rather small in comparison with its sensitivity to nitrogen limitation. Comparing coccolith morphological and geometrical parameters like volume, mass and size to physiological parameters under controlled laboratory conditions is an important step to understand variations in fossil coccolith geometry.